Investigation of laser-driven ionization and dissociation using spin-rotational dynamics - Wangjam, Tomthin Nganba (Kansas State University, 2024)
One of the most important goals of doing research in ultrafast molecular dynamics is to make molecular movies and the reason to make molecular movies is to understand the molecular dynamics which occurs during a chemical reaction. Given the fast timescales of molecular motion, typically ranging from a few nanoseconds to attoseconds and the motion can be only be resolved using ultrafast lasers. In this thesis we will study dynamics in diatomic molecules using the pump-probe technique. We will use an intense pump laser to coherently excite rotational wave-packets in either the ground state of the neutral molecule or low-lying states of the molecular cation and probe the dynamics induced by the pump pulse using photoionization and photodissociation process. Following the previous work done by Makhija et al. and Lam et al. on strong-field ionization after impulsive molecular alignment using a time-domain approach called Orientation Resolution through Rotational Coherence Spectroscopy (ORRCS) we will explore the strong-field ionization process from triplet ground state molecular oxygen. In this thesis, we will expand the work done previously into spin-coupled rotational wave-packets. When spin is coupled to the rotation, the wave packet is no longer purely rotational, and the delay-dependent ionization yield becomes non-periodic. We report the first measurement of such non-periodic dynamics in oxygen. With long delay-dependent data we obtain a high-resolution frequency spectrum after doing Fast Fourier Transform (FFT). With the high resolution frequency spectrum we are able to identify rotational Raman lines from the triplet ground state of molecular oxygen. We have used both time and frequency-domain analysis to gain insights into the role played by spin during strong-field ionization. In the second part of the work we have used time, frequency, and Kinetic energy release spectroscopy with data acquired using the Velocity Map Imaging (VMI) spectrometer touncover the intricate chemical pathways involved in photo-dissociation following a strongfield ionization of oxygen (O₂), nitrogen (N₂), and deuterium (D₂) molecules. With the calculated rotational frequencies and KER from the low-lying potential curves of O₂⁺, N₂⁺, and D₂⁺ cations, we are able to uniquely identify the intermediate electronic states involved. In the O₂⁺ , we have shown the role of the resonant coupling in the 800 nm pump pulses as proposed by Xue et al. with b⁴Σ[subscript g]⁻ state rotational coherences dominating the FFT spectrum. We also found a vibrational Cooper minimum in the O₂⁺ between the intermediate a-state and the dissociative f-state. In both O₂⁺ and N₂⁺ , we have found the strong effect of the few photon resonance-enhanced dissociation with a 264 nm probe. We anticipate that this technique will have broad applicability to ultrafast-laser driven processes in molecules, offering distinct insights into molecular physics and chemistry.
Keywords: Spin rotational coupling; Photoionization; Photodissociation; Strong field induced excitation; Molecular alignment; Pump-probe spectroscopy; Fourier analysis